Penerapan Sistem Manufacturing 4.0 dengan Integrasi Internet of Things (IoT) untuk Optimalisasi Efisiensi Produksi - Zulfadlillah Zulfadlillah; Moh Ayip Fathani; Muhamad Noval; Irwana Irwana (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2024)
Digital technological advancements have driven a paradigm shift towards Industry 4.0, characterized by the integration of cyber-physical systems and artificial intelligence in manufacturing processes. This study analyzes the role of Internet of Things (IoT) in accelerating Manufacturing 4.0 transformation, focusing on production efficiency optimization. Through a systematic literature review of 45 Scopus-indexed journals published between 2019-2024, complemented by experimental analysis on a laboratory-scale smart factory prototype, this research examines the implementation of IoT-based technologies such as predictive maintenance and digital twins. Results demonstrate that IoT integration significantly enhances production efficiency through real-time monitoring (30% downtime reduction), predictive maintenance (20% maintenance cost decrease), and data-driven supply chain optimization (15% energy savings). Case studies from Siemens and PT. Unilever Indonesia confirm that IoT sensor integration with ERP systems improves demand forecasting accuracy by 25% and reduces production errors to 0.001%. Despite challenges including high initial infrastructure costs and cybersecurity vulnerabilities, IoT implementation offers sustainable competitive advantages through enhanced operational efficiency, quality control, and resource management.